AIP Conference Proceedings 2009
DOI: 10.1063/1.3140413
|View full text |Cite
|
Sign up to set email alerts
|

Low Frequency Noises Of Hydrogen Sensors On The Base Of Silicon Having Nano-Pores Layer

Abstract: Sensors have sandwich stracture metal/porous silicon/crystalhne silicon/Al. The contact metal on porous silicon was from Au and from Pd. Porosity of the samples is 57% and 63%. Low frequency noises before, during and after influence of hydrogen gas flow are studied. Noise spectra of the samples in general have Ij f^ forms with 0.7 < / < 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…High sensitivity of spectral dependence of noise to carbon monoxide and ethyl alcohol vapors concentration of the sensors made on metal-porous Si-crystalline Si-metal sensors are observed [5]. It also observed the growth of the frequency index γ of the 1/f-noise Hooge formula: 0.5 in air, 0.85 for the air mixed with ethyl alcohol vapors; 1 for the air mixed 0.1% H 2 , and 1.3 for the air mixed with 0.4% CO [5] [10]. For describing noise fluctuation in gas sensors, several models are proposed: a model of adsorption-desorption noise in metal-oxide gas sensors using Langmuir's and Wolkenstein theories [11] [12], "Correlated number-mobility fluctuation model" [10].…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…High sensitivity of spectral dependence of noise to carbon monoxide and ethyl alcohol vapors concentration of the sensors made on metal-porous Si-crystalline Si-metal sensors are observed [5]. It also observed the growth of the frequency index γ of the 1/f-noise Hooge formula: 0.5 in air, 0.85 for the air mixed with ethyl alcohol vapors; 1 for the air mixed 0.1% H 2 , and 1.3 for the air mixed with 0.4% CO [5] [10]. For describing noise fluctuation in gas sensors, several models are proposed: a model of adsorption-desorption noise in metal-oxide gas sensors using Langmuir's and Wolkenstein theories [11] [12], "Correlated number-mobility fluctuation model" [10].…”
Section: Introductionmentioning
confidence: 76%
“…It also observed the growth of the frequency index γ of the 1/f-noise Hooge formula: 0.5 in air, 0.85 for the air mixed with ethyl alcohol vapors; 1 for the air mixed 0.1% H 2 , and 1.3 for the air mixed with 0.4% CO [5] [10]. For describing noise fluctuation in gas sensors, several models are proposed: a model of adsorption-desorption noise in metal-oxide gas sensors using Langmuir's and Wolkenstein theories [11] [12], "Correlated number-mobility fluctuation model" [10]. For the bio-chemical sensors, we also have proposed trapping-detraping (adsorption-desorption) and charge fluctuation models [13] [14].…”
Section: Introductionmentioning
confidence: 81%
“…Phenomenon of low frequency (LF) fluctuations of electric current in semiconductors and semiconductor devices is an object of investigations of many researchers and engineers [9][10][11][12][13][14]. Studies have shown that behavior and magnitude of LF-noise in devices based on nanosize porous silicon differs essentially from the noise in devices based on crystalline silicon [10][11][12]. Since the sensors based on porous silicon, are very sensitive to different gases present in environment, the level and frequency dependence of LF-noises in these sensors also depends on the type and concentration of these gases.…”
Section: Introductionmentioning
confidence: 99%